On a p⋅-biharmonic problem of Kirchhoff type involving critical growth. Issue 16 (2nd November 2022) - Chung, Nguyen Thanh; Ho, Ky
ABSTRACT: We establish a concentration-compactness principle for the Sobolev space W 2, p ( ⋅ ) ( Ω ) ∩ W 0 1, p ( ⋅ ) ( Ω ) that is a tool for overcoming the lack of compactness of the critical Sobolev imbedding. Using this result, we obtain several existence and multiplicity results for a class of Kirchhoff type problems involving p ( ⋅ ) -biharmonic operator and critical growth.